Update in autoimmune and paraneoplastic myelopathies: Newly described antigen targets and antibody testing - Passeri, Michlene; Matthews, Elizabeth; Kammeyer, Ryan; Piquet, Amanda L. (Frontiers in Neurology, 2022)
Myelopathy is an increasingly recognized presentation of many antibody-mediated neuroinflammatory disorders. While specific features of certain autoimmune myelopathies such as aquaporin-4 antibody associated neuromyelitis optica spectrum disorder (NMOSD) and myelin oligodendrocyte glycoprotein associated disorder (MOGAD) are well-characterized, other less commonly seen antibody-associated myelopathies are not as well-defined. These include but are not limited to, Hu/ANNA1, anti-glial fibrillary acidic protein (GFAP), anti-CV2/collapsin response mediator protein (CRMP5), and amphiphysin. Here, we review the mentioned more common antibody mediated myelopathies as well those that as less common, followed by a review of differentials that may mimic these disorders.